1989
DOI: 10.1080/02681218980000211
|View full text |Cite
|
Sign up to set email alerts
|

In situlocalization of T lymphocyte subsets in human paracoccidioidomycosis

Abstract: lmmunohistochemical techniques using monoclonal antibodies to T lymphocyte subsets were used to characterize granulomas caused by Paracoccidioides brasiliensis. Punch biopsies of skin or mucosa from eight patients and of lymph nodes from two patients with disseminated paracoccidioidomycosis were studied. The T lymphocytes were distributed either in a localized pattern related to epithelioid granulomas or in a diffuse arrangement, predominantly around the vessels. In the granulomas, T cells formed a peripheral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 16 publications
2
18
0
1
Order By: Relevance
“…Some authors observed decreased numbers of CD4 ϩ and CD8 ϩ T cells (30), whereas others reported a decrease only in the CD4 ϩ subset (2). The mucous and skin granulomatous lesions of PCM patients presented an elevated CD4/CD8 T-cell ratio due to high numbers of infiltrating CD4 ϩ T cells; this ratio in the blood, however, was very low (29). These findings showed that the phenotype of cells found in the blood does not reflect the subsets infiltrating the lesions.…”
Section: Discussionmentioning
confidence: 40%
“…Some authors observed decreased numbers of CD4 ϩ and CD8 ϩ T cells (30), whereas others reported a decrease only in the CD4 ϩ subset (2). The mucous and skin granulomatous lesions of PCM patients presented an elevated CD4/CD8 T-cell ratio due to high numbers of infiltrating CD4 ϩ T cells; this ratio in the blood, however, was very low (29). These findings showed that the phenotype of cells found in the blood does not reflect the subsets infiltrating the lesions.…”
Section: Discussionmentioning
confidence: 40%
“…Immunohistochemical staining techniques using monoclonal antibodies specific for CD4 and CD8 T cells revealed a predominance of CD4 T cells in granulomas from patients with the acute and chronic forms of the disease (200). CD4/CD8 ratios in granulomas were higher in biopsy samples from lymph nodes (3.8 to 4.0) and skin (1.27 to 4.27) than in those from mucosa (1.01 to 2.76).…”
Section: Lymphocytesmentioning
confidence: 94%
“…A strong argument in support of this hypothesis is that impairment of cell-mediated responses is reversible by successful therapy (197,264). The search for a factor(s) responsible for negative immunoregulation of cellular immunity during paracoccidioidomycosis has ranged from unidentified inhibitory factors in patient plasma (208,264) and immune complexes (9,68,69,304) to an imbalance in T-cell subsets (200,204).…”
Section: Cell-mediated Responsesmentioning
confidence: 99%
“…Oral mucosal lesions are commonly multiple, with a granular, mulberry-like surface and microulcerations, and microscopically are observed as a granulomatous inflammatory reaction and pseudoepitheliomatous hyperplasia that can be mistaken as neoplastic (Kaminagakura et al, 2006;Moscardi-Bacchi et al, 1989;Scully & de Almeida, 1992), which can be a problem clinically as the oral lesions of PCM closely resemble carcinoma (Kaminagakura et al, 2006). The fungus may use a sequence of different mechanisms to become established in the host, from the first contact with host cells until the later stages of the disease.…”
Section: Introductionmentioning
confidence: 99%